2021
DOI: 10.3389/fevo.2021.767102
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Biology of Takydromus kuehnei Indicates Tropical Lizards From High Elevation Have Not Been Severely Threatened by Climate Change

Abstract: Climate change poses different threats to animals across latitudes. Tropical species have been proposed to be more vulnerable to climate change. However, the responses of animals from tropical mountains to thermal variation and climate change have been scarcely studied. Here, we investigated the thermal biology traits of a tropical lizard (Takydromus kuehnei) distributed at high elevations (>950 m) and evaluated the vulnerabilities of T. kuehnei by thermal biology traits, thermal safety margin, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Correa Ayram et al, 2017;Golicher et al, 2008;Ponce-Reyes et al, 2017, 2013. Similar outcomes have been forecast for other montane regions, including Costa Rica (Colwell et al, 2008), the tropical Andes (Ledo, Montes & Condes, 2009;Tejedor-Garavito et al, 2015;Godoy-Bürki, 2016), the 'campos rupestres' (Bitencourt et al, 2016) and the Atlantic forest biomes in Brazil (Castro et al, 2020), the Neotropical realm as a whole (Helmer et al, 2019), the Western Ghats region in India (Chakraborty et al, 2013), China's Abies forests (Liao et al, 2020), Myanmar's natural protected areas (Nwe, Zomer & Corlett, 2020), and the Australian Wet Tropics (Costion et al, 2015).…”
Section: (B) General Decline Of Tmfssupporting
confidence: 56%
See 1 more Smart Citation
“…Correa Ayram et al, 2017;Golicher et al, 2008;Ponce-Reyes et al, 2017, 2013. Similar outcomes have been forecast for other montane regions, including Costa Rica (Colwell et al, 2008), the tropical Andes (Ledo, Montes & Condes, 2009;Tejedor-Garavito et al, 2015;Godoy-Bürki, 2016), the 'campos rupestres' (Bitencourt et al, 2016) and the Atlantic forest biomes in Brazil (Castro et al, 2020), the Neotropical realm as a whole (Helmer et al, 2019), the Western Ghats region in India (Chakraborty et al, 2013), China's Abies forests (Liao et al, 2020), Myanmar's natural protected areas (Nwe, Zomer & Corlett, 2020), and the Australian Wet Tropics (Costion et al, 2015).…”
Section: (B) General Decline Of Tmfssupporting
confidence: 56%
“…The prospect for ectotherms is a matter of much concern. Thermal tolerance experiments (LoE1b) conducted with amphibians (Rueda‐Solano et al ., 2016; von May et al ., 2017; González‐del‐Pliego et al ., 2020), reptiles (Muñoz et al ., 2016; Piantoni, Navas & Ibargüengoytía, 2016; Strangas et al ., 2019; but see Tao et al ., 2021) and insects (e.g. Montejo‐Kovacevich et al ., 2020; Polato et al ., 2018; Shah et al ., 2017 b ) showed that tropical montane species are more susceptible to changes in temperature regimes relative to their lowland or temperate counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, T. kuehnei from high elevation (i.e. greater than 900 m) has not been severely threatened by climate warming [93]. Apart from these kinds of large-scale geographical (e.g.…”
Section: Discussionmentioning
confidence: 99%